PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB BERBASIS SMART TV BERBANTU APLIKASI EDUKASI UNTUK SISWA KELAS 2 SDIT INSAN RABBANI TEGALSARI GADINGREJO - Redita Ayu Kesuma; Maya Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Fruit-themed Arabic language learning media in class II SDIT Insan Rabbani Tegalsari Gadingrejo actually already exists, but has not been utilized optimally. This research uses the Research and Development (R&D) method with the ADDIE development model. The research objective is to develop Smart TV-based media with the help of the Canva AI application to increase students' interest in learning. The trial involved 26 students and showed that the media developed was valid, practical and useful. As a result, students' interest in learning increases, thus, this media can help increase interest in learning while making it easier for students to understand Arabic vocabulary about fruit